Graft copolymer of tannin and polyvinyl alcohol with acrylic acid for the preparation of hydrophobic biodegradable film - Xu, Xuan; Xu, Ying; Deng, Shuduan; Chen, Xinyi; Essawy, Hisham; Lee, Seng Hua; Lum, Wei Chen; Zhou, Xiaojian; Zhang, Jun (Elsevier BV, 2024)
Using CaCl2-H2O2 as the initiator, hydrophobic tannin-acrylic resin (TA) was prepared by grafting acrylic monomers onto tannins through redox reaction. Subsequently, biodegradable TA-polyvinyl alcohol (PVOH) hydrophobic film (TAP) was prepared by blending TA with PVOH at room temperature. The results of Fourier transform infrared spectroscopy (FT-IR) and Electro Spray Ionization Mass Spectroscopy (ESI-MS) showed that polypropylene undergoes graft copolymerization at position 8 of the A-ring in tannin and acrylic monomers. The results of Gel Permeation Chromatography (GPC) showed that the blending of TA resin with PVOH resulted in a higher molecular weight and denser network structure of the film. The preparation process of TAP film is simple, with room temperature curing and no surface pores and cracks. Moreover, the addition of TA transforms hydrophilic PVOH films into hydrophobic films, with a water contact angle of up to 110°. At the same time, TAP films have higher Brinell hardness and elongation at break compared to PVOH film. In addition, thermogravimetric analyzer (TG) and ultraviolet visible light (UV–Vis) measurements showed that the TAP film has good thermal stability and excellent resistance to UV–Vis. More importantly, the TAP film was found to have good biodegradability against Penicillium sp. Scanning electron microscopy (SEM) observed that the TAP film was degraded by Penicillium sp. after 15-days exposure.